Intubation Related Laryngeal Injuries in Pediatric Population - Lambercy, Karma; Pincet, Laurence; Sandu, Kishore (Frontiers in Pediatrics, 2021)
Introduction : Laryngeal intubation related lesions (LIRL) in pediatric patients cause extreme morbidity in both elective and emergency settings. It has a wide range of presentations from minor laryngeal edema to a life-threatening airway obstruction. We report here our units’ experience with LIRL in neonates, infants, and small children. Material and Methods: This is a retrospective monocentric cohort study between January 2013 and April 2019. Results: Thirty-nine patients with intubation lesions were included in the study. We looked at the lesions type, characteristics, management, and outcome. Half the patients were premature and having comorbidities. Main LIRL were subglottic stenosis (31%), ulcers (26%), granulations (18%), retention cysts (18%), posterior glottic stenosis (13%) and vocal cords edema (5%). Unfavorable lesions causing airway stenosis were associated with an intubation duration of over one week and were an important factor in causing airway stenosis (p<0,05). The endoscopic treatment performed for these lesions was lesion and anatomical site-specific. Tracheostomy was needed in five patients, and was avoided in another two. Seven patients (18%) received open surgery prior to their decannulation. Conclusions: LIRL management is challenging and stressful in the pediatric population and optimal treatment could avoid extreme morbidity in them. Intubation duration and associated comorbidities are important factors in deciding the severity of these lesions. Protocols to prevent the formation of these lesions are critical.